Influence of Extra Supplementation with Arginine and Lysine on Overall Performance, Ovarian Activities and Humoral Immune Response in Local Saudi Hens - Basiouni, G.; Najib, H.; Zaki, M.M.; Al-Ankari, A.S. (International Journal of Poultry Science, 2006)
This study was designed to investigate the effect of increasing level(s) of arginine (ARG) and/or lysine (LYS) over the normal requirements of the Leghorn breeds (NRC, 1994) and their interaction on performance, ovarian activity and humoral immune response of local Saudi chickens known for their low production. The outcome of the study revealed that feed intake and specific gravity of the eggs were the only traits significantly (P< 0.05) affected by the interaction between ARG and LYS. Hen-day production did not significantly (P>0.05) increase and feed conversion improved with the higher levels of ARG and LYS (1.54 and 2.05 %, respectively) compared to the controls. In spite of the significant effect of specific gravities of the eggs, no specific trend was found in response to the treatments. Albumen height was better in the control group in both treatments which supported the higher egg size of the control group compared to the other treatments. No significant differences were found among treatments or their interaction in all ovarian and oviductal measurements. However there was a tendency for an increase in the weight of F1 follicles (largest follicles) as a result of ARG supplementation at the 2.04 % level. The study of humoral immune response of the birds revealed that mean antibodies titers (MAT) at week 24, 28, 32 and 40 of age were nearly the same in all groups of birds and no significant differences between the groups in the designated periods (P>0.05). However, at week 36 of age, MAT of group treated with 1.54% ARG and 1.05% LYS were significantly higher than the controls (P< 0.05). A significant correlation between MAT and thymus weight index at week 40 of age was observed. Based on the results of this study, it is concluded that extra ARG, LYS and their interaction did not significantly affect performance and ovarian activity of the local birds but enhanced thymus size and maintain MAT level over time.